2008
DOI: 10.17744/mehc.30.2.g662g5l2r1352198
|View full text |Cite
|
Sign up to set email alerts
|

Asian American Students’ Cultural Values, Stigma, and Relational Self-construal: Correlates of Attitudes Toward Professional Help Seeking

Abstract: In this study, we investigated how adherence to Asian values, stigma of receiving psychological help, relational-interdependent self-construal, age and gender, for Asian American college and graduate students, singly and in concert predicted attitudes toward seeking professional psychological help. We also examined how stigma mediates the effect of adherence to Asian values on help-seeking attitudes. Correlational and multiple regression analyses determined that lower adherence to Asian values, lower levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
243
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(278 citation statements)
references
References 47 publications
28
243
4
3
Order By: Relevance
“…Many studies found that cultural mistrust resulted in a preference by Black clients for Black counselors, negative attitudes toward seeking psychological treatment, and a propensity to terminate therapy prematurely (Sue & Sue, 1972;Townes, Chavez-Korell, & Cunningham, 2009). These findings have been generalized to other minority groups including Southeast Asians and Latinos (David, 2010;Shea & Yeh, 2008).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 63%
See 1 more Smart Citation
“…Many studies found that cultural mistrust resulted in a preference by Black clients for Black counselors, negative attitudes toward seeking psychological treatment, and a propensity to terminate therapy prematurely (Sue & Sue, 1972;Townes, Chavez-Korell, & Cunningham, 2009). These findings have been generalized to other minority groups including Southeast Asians and Latinos (David, 2010;Shea & Yeh, 2008).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 63%
“…Minorities in the U.S. have historically experienced racism, discrimination, and oppression to the extent that these experiences have negatively influenced mental health help-seeking (Chung & Bemak, 2012;Obasi & Leong, 2009;Shea & Yeh, 2008). Initially developed as a concept to describe the distrust Black Americans had towards White Americans, cultural mistrust encompasses an overall mistrust of White-dominated institutions such as the legal system, educational system, job settings, and government agencies (David, 2010).…”
Section: Cultural Mistrust Of Mental Health Counselorsmentioning
confidence: 99%
“…Stigma and its detrimental effect on mental health help-seeking behavior s has been documented in developed countries (Alvidrez, Snowden, & Kaiser, 2008;Cooper, Corrigan, & Watson, 2003;Corrigan, 2004) and among Asian cultures (Fogel & Ford, 2005;Miville & Constantine, 2007;Shea & Yeh, 2008). Culture also plays a big role in shaping attitudes and social interactions with individuals with mental illness, as well as in its treatment (Abdullah & Brown, 2011).…”
Section: Public and Private Stigma Hiya And Loss Of Facementioning
confidence: 99%
“…Örneğin, Asya kökenli Amerikalı lisans ve lisansüstü öğrencilerle yapılan bir çalışmada (Shea ve Yeh, 2008), profesyonel psikolojik yardım aramaya ilişkin tutumlar ile kültürel değerler, damgalama ve benlik kurgusu arasındaki ilişkiler incelenmiştir. Araştırma sonucunda, düşük düzeyde damgalama ve yüksek düzeyde ilişkisel-karşılıklı bağımlı benlik kurgusunun, psikolojik yardım aramaya ilişkin olumlu tutumlarla ilişkili olduğu saptanmıştır.…”
unclassified